End humanitarian nightmares with a cold chain logistics strategy - Abikova, Jana (London : SAGE Publications: SAGE Business Cases Originals, 2024)
Sara, the head of logistics for an international humanitarian organization, must find the safest, most effective way to deliver vaccines to a number of locations in South Sudan experiencing an outbreak of measles, one of the deadliest, vaccine-preventable diseases. Speed is essential. So is protecting the vaccine from damage. Emergency situations, however, mean unpredictability, uncertainty, and unconventional conditions. This case enables students to put themselves in Sara’s shoes to plan a successful emergency vaccine delivery strategy using a logistics method known as cold chain management.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business logistics -- Case studies; Humanitarian assistance -- South Sudan -- Case studies; Measles vaccine -- South Sudan -- Case studies